A kind of light and high-strength foamed concrete and preparation method thereof
By using a composite foaming agent of diosgenin and modified keratin powder and composite fibers in foam concrete, the problems of high density, poor thermal insulation and insufficient strength of foam concrete are solved, and lightweight and high-strength foam concrete is achieved, which is suitable for Wide range of construction and civil engineering applications.
Patent Information
- Application Number
- CN202410651383.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-05-24
AI Technical Summary
The existing foam concrete has insufficient density, insufficient thermal insulation as much as foam plastics, and poor strength in applications, which limits its large-scale production and application in construction and civil engineering.
The preparation method of lightweight high -strength foam concrete is used to improve the mechanical strength and foam of concrete mechanical strength and foam through specific component proportions and processing methods, including using potato sauce and modified protein powder, as well as composite fibers, and composite fibers. stability.
The light and high -strength foam concrete is realized, which has high pressure resistance and anti -folding strength. At the same time, the stability and thermal insulation performance of the foam have also been improved. It is suitable for extensive buildings and civil engineering applications.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete and relates to a lightweight high-strength foam concrete and a preparation method thereof. Background Art
[0002] Foamed concrete, also known as air bubble concrete, is a special type of aerated concrete and belongs to lightweight thermal insulation materials. The general conventional application areas are mainly building thermal insulation, civil engineering and geotechnical engineering backfill, etc., where foamed concrete is used the most. In these aspects, foamed concrete has advantages and has developed rapidly in my country, with construction volume ranking first in the world.
[0003] In the past, people only used it as a thermal insulation material, but in recent years, it has been discovered that it has so many special functions, such as energy absorption, shock and explosion resistance, sound insulation and sound absorption, electromagnetic wave absorption, water permeability and filtration, anti-seepage and moisture resistance, water retention and greening, fire resistance, fire prevention, anti-scouring and protection, floating load-bearing, etc. Judging from the number of functions, it should be one of the most excellent new functional materials. The discovery of these functions has made its use more and more extensive and has attracted the attention of all walks of life. Foam concrete blocks have always been the first key product that all parties in China are keen on. However, due to the poor strength of natural curing products and large shrinkage in the later period, this product has never been produced and applied on a large scale in my country. In addition, it has three major shortcomings: high density, inferior thermal insulation to foam plastics, and poor strength. In order for foam concrete to be popularized and applied, the above key technical problems should be focused on. Summary of the invention
[0004] The main purpose of the present invention is to provide a lightweight and high-strength foamed concrete and a preparation method thereof. The concrete provided by the present invention has the advantages of lightweight effect and high mechanical strength.
[0005] The present invention adopts the following technical solutions to achieve the above purpose:
[0006] A lightweight high-strength foamed concrete comprising the following components in parts by weight:
[0007] 50-80 parts of silicate cement, 8-12 parts of fly ash, 12-15 parts of composite foaming agent, 3-5 parts of silica sol, 40-60 parts of quartz sand, 3-5 parts of composite fiber, 2-5 parts of hydroxypropyl methylcellulose, and 30-50 parts of water.
[0008] Furthermore, the composite foaming agent contains diosgenin and modified keratin powder; the weight ratio of diosgenin to modified keratin powder is (0.2-0.5):1.
[0009] Furthermore, the preparation method of the modified keratin powder is as follows: the keratin powder is soaked in a hydrogen peroxide solution and a phytic acid solution for 5-6 hours respectively, and then dried, thioglycolic acid, ethylene glycol, and chitosan are added, and the mixture is oscillated at a constant temperature for 1 hour at 50° C. in a nitrogen atmosphere, and then the temperature is raised to 60° C., sodium thiosulfate is added, and the mixture is oscillated at a constant temperature for 4-6 hours. After the reaction is completed, the mixture is washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0010] Furthermore, in the above-mentioned method for preparing modified keratin powder, the volume fraction of the hydrogen peroxide solution is 60%; and the volume fraction of the phytic acid solution is 50%.
[0011] Furthermore, in the above-mentioned modified keratin powder preparation method, the mass-volume ratio of keratin powder, hydrogen peroxide solution, phytic acid solution, thioglycolic acid, ethylene glycol, chitosan, and sodium thiosulfate, in terms of kg / L / L / L / L / kg / kg, is 1:(1-1.2):(1-1.2):(1.2-1.5):(0.5-0.8):(0.3-0.5):(0.05-0.08).
[0012] Furthermore, the preparation method of the composite fiber is as follows:
[0013] The glass fiber, polypropylene fiber and fatty alcohol polyoxyethylene ether are stirred and mixed at 80-100°C and 100-120r / min for 30 minutes, then heated to a molten state and drawn to obtain composite fibers.
[0014] Furthermore, in the above-mentioned method for preparing the composite fiber, the weight ratio of glass fiber, polypropylene fiber and fatty alcohol polyoxyethylene ether is 1:(0.3-0.8):(1-1.2).
[0015] The present invention provides a method for preparing the above concrete, comprising the following steps:
[0016] Step A, mixing silicate cement, fly ash, quartz sand, composite fiber and water to obtain cement slurry;
[0017] Step B, adding water to the composite foaming agent to foam in a foaming machine, adding it to the cement slurry obtained in step A and mixing evenly, then adding silica sol and hydroxypropyl methylcellulose, mixing evenly, pouring it into a mold, steam curing after molding, and obtaining concrete.
[0018] The present invention has the following beneficial effects:
[0019] 1. The composite foaming agent of diosgenin and modified keratin powder of the present invention, in the preparation method of the modified keratin powder, firstly, hydrogen peroxide and phytic acid are used for protein pretreatment to change the pH value and surface microstructure of the protein to a certain extent, and then thiol treatment is carried out, and chitosan and ethylene glycol are grafted to introduce hydrophilic groups to increase the solubility of keratin. The hydrophilic groups and the hydrophobic groups on the surface of the protein act together to make the bubbles formed subsequently less likely to collapse, thereby helping to improve the bubble capacity of the foaming agent and the stability of the foam; the presence of diosgenin can help to improve the dispersibility. Under the auxiliary effect of diosgenin, the foaming agent can form a relatively tight film and stable foam, improve the foam pore size, optimize the pore structure density, make the formed foam dense and not easy to collapse, make the foaming agent have excellent foaming ability, and the foamed concrete formed when used for concrete has no mold collapse phenomenon and good stability.
[0020] 2. The present invention uses composite fibers, glass fibers and polypropylene fibers cooperate with each other, polypropylene fibers make up for the brittleness of glass fibers, and glass fibers improve the bonding properties of polypropylene fibers. The composite fibers formed by the two can significantly improve the bonding with the cement base.
[0021] 3. The foamed concrete prepared by the present invention has the characteristics of high strength, low bulk density, etc., outstanding comprehensive performance and a wide range of applications. DETAILED DESCRIPTION
[0022] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.
[0023] Example 1 Lightweight high-strength foam concrete
[0024] Preparation of modified keratin powder: 10 kg of keratin powder was soaked in 12 L of 60% by volume hydrogen peroxide solution and 10 L of 50% by volume phytic acid solution for 5 h respectively and then dried. 12 L of thioglycolic acid, 8 L of ethylene glycol and 3 kg of chitosan were added to the keratin powder, and the mixture was oscillated at a constant temperature at 50° C. for 1 h in a nitrogen atmosphere. The mixture was then heated to 60° C., 0.8 kg of sodium thiosulfate was added, and the mixture was oscillated at a constant temperature for 6 h. After the reaction, the mixture was washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0025] Preparation of composite fiber: 10 kg of glass fiber, 8 kg of polypropylene fiber and 10 kg of fatty alcohol polyoxyethylene ether were stirred and mixed at 80°C and 120 r / min for 30 min, then heated to a molten state and drawn to obtain composite fiber.
[0026] Concrete preparation:
[0027] Step A, 80 kg of Portland cement, 12 kg of fly ash, 60 kg of quartz sand, 5 kg of the composite fiber prepared above, and 35 kg of water are mixed uniformly to obtain cement slurry;
[0028] Step B: add 2kg of diosgenin and 10kg of the modified keratin powder prepared above into 10kg of water and foam them in a foam machine, add them into the cement slurry obtained in step A and mix them evenly, then add 5kg of silica sol and 5kg of hydroxypropyl methylcellulose, mix them evenly, pour them into a mold, steam cure them after molding, and obtain concrete.
[0029] Example 2 Lightweight high-strength foam concrete
[0030] Preparation of modified keratin powder: 10 kg of keratin powder was soaked in 10 L of 60% by volume hydrogen peroxide solution and 12 L of 50% by volume phytic acid solution for 6 h respectively and then dried. 15 L of thioglycolic acid, 5 L of ethylene glycol and 5 kg of chitosan were added to the keratin powder, and the mixture was oscillated at a constant temperature at 50° C. for 1 h in a nitrogen atmosphere. The mixture was then heated to 60° C., 0.5 kg of sodium thiosulfate was added, and the mixture was oscillated at a constant temperature for 4 h. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0031] Preparation of composite fiber: 10 kg of glass fiber, 3 kg of polypropylene fiber and 12 kg of fatty alcohol polyoxyethylene ether were stirred and mixed at 100°C and 100 r / min for 30 min, then heated to a molten state and drawn to obtain composite fiber.
[0032] Concrete preparation:
[0033] Step A, 50 kg of Portland cement, 8 kg of fly ash, 40 kg of quartz sand, 3 kg of the composite fiber prepared above, and 20 kg of water are mixed evenly to obtain cement slurry;
[0034] Step B: 5 kg of diosgenin and 10 kg of the modified keratin powder prepared above are added with 15 kg of water to foam in a foam machine, and then added to the cement slurry obtained in step A and mixed evenly, and then 3 kg of silica sol and 2 kg of hydroxypropyl methylcellulose are added, mixed evenly, poured into a mold, and steam cured after molding to obtain concrete.
[0035] Example 3 Lightweight high-strength foam concrete
[0036] Preparation of modified keratin powder: 10 kg of keratin powder was soaked in 11 L of 60% by volume hydrogen peroxide solution and 11 L of 50% by volume phytic acid solution for 6 hours respectively, and then dried. The keratin powder was added with 13 L of thioglycolic acid, 6 L of ethylene glycol, and 4 kg of chitosan, and oscillated at a constant temperature at 50° C. in a nitrogen atmosphere for 1 hour. The temperature was then raised to 60° C., 0.6 kg of sodium thiosulfate was added, and the mixture was oscillated at a constant temperature for 6 hours. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0037] Preparation of composite fiber: 10 kg of glass fiber, 5 kg of polypropylene fiber and 11 kg of fatty alcohol polyoxyethylene ether were stirred and mixed at 80°C and 120 r / min for 30 min, then heated to a molten state and drawn to obtain composite fiber.
[0038] Concrete preparation:
[0039] Step A, 60 kg of Portland cement, 10 kg of fly ash, 50 kg of quartz sand, 4 kg of the composite fiber prepared above, and 30 kg of water are mixed evenly to obtain cement slurry;
[0040] Step B: 3kg of diosgenin and 10kg of the modified keratin powder prepared above are added with 15kg of water to foam in a foam machine, and then added to the cement slurry obtained in step A and mixed evenly, and then 4kg of silica sol and 3kg of hydroxypropyl methylcellulose are added, mixed evenly, poured into a mold, and steam cured after molding to obtain concrete.
[0041] Comparative Example 1 Preparation of Foamed Concrete
[0042] Preparation of modified keratin powder: 10 kg of keratin powder was soaked in 11 L of 60% ethanol solution by volume for 6 h and then dried. 13 L of thioglycolic acid was added to the keratin powder, and the mixture was oscillated at a constant temperature of 50° C. in a nitrogen atmosphere for 1 h. The mixture was then heated to 60° C., 0.6 kg of potassium persulfate was added, and the mixture was oscillated at a constant temperature for 6 h. After the reaction, the mixture was washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0043] Concrete preparation:
[0044] Step A, 60 kg of Portland cement, 10 kg of fly ash, 50 kg of quartz sand, 2 kg of glass fiber, 2 kg of polypropylene fiber and 30 kg of water are mixed evenly to obtain cement slurry;
[0045] Step B: 3kg of diosgenin and 10kg of the modified keratin powder prepared above are added with 15kg of water to foam in a foam machine, and then added to the cement slurry obtained in step A and mixed evenly, and then 4kg of silica sol and 3kg of hydroxypropyl methylcellulose are added, mixed evenly, poured into a mold, and steam cured after molding to obtain concrete.
[0046] Comparative Example 2 Preparation of Foamed Concrete
[0047] Preparation of composite fiber: 10 kg of glass fiber, 5 kg of polypropylene fiber and 11 kg of fatty alcohol polyoxyethylene ether were stirred and mixed at 80°C and 120 r / min for 30 min, then heated to a molten state and drawn to obtain composite fiber.
[0048] Concrete preparation:
[0049] Step A, 60 kg of Portland cement, 10 kg of fly ash, 50 kg of quartz sand, 4 kg of the composite fiber prepared above, and 30 kg of water are mixed evenly to obtain cement slurry;
[0050] Step B: add 3kg of diosgenin and 10kg of keratin powder to 15kg of water for foaming in a foam machine, add to the cement slurry obtained in step A and mix well, then add 4kg of silica sol and 3kg of hydroxypropyl methylcellulose, mix well, pour into a mold, steam cure after molding, and obtain concrete.
[0051] Comparative Example 3 Preparation of Foamed Concrete
[0052] Preparation of modified keratin powder: 10 kg of keratin powder was soaked in 11 L of 60% by volume hydrogen peroxide solution and 11 L of 50% by volume phytic acid solution for 6 hours respectively, and then dried. The keratin powder was added with 13 L of thioglycolic acid, 6 L of ethylene glycol, and 4 kg of chitosan, and oscillated at a constant temperature at 50° C. in a nitrogen atmosphere for 1 hour. The temperature was then raised to 60° C., 0.6 kg of sodium thiosulfate was added, and the mixture was oscillated at a constant temperature for 6 hours. After the reaction was completed, the mixture was washed with anhydrous ethanol and dried to obtain the modified keratin powder.
[0053] Preparation of composite fiber: 10 kg of glass fiber and 11 kg of fatty alcohol polyoxyethylene ether were stirred and mixed at 80° C. and 120 r / min for 30 min, then heated to a molten state and drawn to obtain composite fiber.
[0054] Concrete preparation:
[0055] Step A, 60 kg of Portland cement, 10 kg of fly ash, 50 kg of quartz sand, 4 kg of the composite fiber prepared above, and 30 kg of water are mixed evenly to obtain cement slurry;
[0056] Step B: add 15 kg of water to 10 kg of modified keratin powder in a foaming machine to foam, add to the cement slurry obtained in step A and mix well, then add 4 kg of silica sol and 3 kg of hydroxypropyl methylcellulose, mix well, pour into a mold, steam cure after molding, and obtain concrete.
[0057] Performance Testing
[0058] 1. Foaming agent performance test
[0059] The composite foaming agent (modified keratin powder, diosgenin) in Examples 1-3, the foaming agent (modified keratin powder, diosgenin) in Comparative Example 1, the foaming agent (keratin powder, diosgenin) in Comparative Example 2, the foaming agent (modified keratin powder) in Comparative Example 3, and the commercially available foaming agent were tested for foaming time, foam volume, 1h settlement distance, 1h water exudation, and foam uniformity index according to the relevant provisions of JG / T 266-2011 "Foamed Concrete".
[0060] Table 1 Comparison of foaming agent properties
[0061] Foaming agent Foaming multiple 1h Settlement distance (mm) 0.5h water secretion (g / L) Example 1 38 1.8 13.3 Example 2 35 2.2 12.5 Example 3 36 1.6 13.7 Comparative Example 1 33 2.9 15.1 Comparative Example 2 23 3.7 17.1 Comparative Example 3 28 3.1 16.4 Commercially available 25 3.5 17.3
[0062] As shown in Table 1, the composite foaming agent prepared by the present invention has excellent foaming ability, high foaming multiple and high stability, and the foam is not easy to collapse. When used in foamed concrete, it has high stability and the concrete has no mold collapse. In Comparative Example 1, the keratin powder is modified in different ways, the keratin powder is not modified in Comparative Example 2, and the foaming agent in Comparative Example 3 does not contain diosgenin, and the foaming performance of the foaming agent deteriorates to varying degrees.
[0063] 2. Concrete performance test
[0064] Finished concrete was prepared according to the preparation method described in Examples 1-3 and Comparative Examples 1-3, and standard test blocks were prepared with reference to the method in GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the compressive strength, flexural strength and bulk density of the concrete were tested for 28 days.
[0065] Table 2 Concrete performance comparison
[0066] Concrete <![CDATA[Unit weight (kg / m 3 )]]> 28-day compressive strength (MPa) 28-day flexural strength (MPa) Example 1 1462 12.3 4.1 Example 2 1507 11.6 3.7 Example 3 1484 12.5 4.3 Comparative Example 1 1536 10.3 3.1 Comparative Example 2 1561 9.9 2.6 Comparative Example 3 1624 9.6 3.3
[0067] As can be seen from Table 2, the concrete produced by the present invention has a lightweight effect and high compressive strength and flexural strength. In Comparative Example 1, the keratin powder is modified in a different way and the composite fiber of the present invention is not used in the concrete. In Comparative Example 2, the keratin is not modified, the foaming agent in Comparative Example 3 does not contain diosgenin, and the composite fiber preparation method is different, so that the bulk density of the prepared concrete increases to varying degrees, and the compressive and flexural strengths decrease to varying degrees. It can be seen that the components in the concrete of the present invention work synergistically to achieve the effect of lightweight and high strength.
Claims
1. A lightweight and high-strength foamed concrete, characterized in that: Contains the following components in parts by weight: 50-80 parts of Portland cement, 8-12 parts of fly ash, 12-15 parts of composite foaming agent, 3-5 parts of silica sol, 40-60 parts of quartz sand, 3-5 parts of composite fiber, 2-5 parts of hydroxypropyl methylcellulose, and 30-50 parts of water; The composite foaming agent contains diosgenin and modified keratin powder in a weight ratio of (0.2-0.5):1; The preparation method of the modified keratin powder is as follows: keratin powder is sequentially soaked in a 60% by volume hydrogen peroxide solution and a 50% by volume phytic acid solution for 5-6 hours, then dried, thioglycolic acid, ethylene glycol and chitosan are added, constant temperature oscillation is performed at 50° C. in a nitrogen atmosphere for 1 hour, then the temperature is raised to 60° C., sodium thiosulfate is added, constant temperature oscillation is performed for 4-6 hours, and after the reaction is completed, the modified keratin powder is washed with anhydrous ethanol and dried to obtain the modified keratin powder; wherein the mass-volume ratio of keratin powder, hydrogen peroxide solution, phytic acid solution, thioglycolic acid, ethylene glycol, chitosan and sodium thiosulfate is 1:(1-1.2):(1-1.2):(1.2-1.5):(0.5-0.8):(0.3-0.5):(0.05-0.08) in terms of kg / L / L / L / L / kg / kg. The preparation method of the composite fiber is: The glass fiber, polypropylene fiber and fatty alcohol polyoxyethylene ether are stirred and mixed at 80-100° C. and 100-120 r / min for 30 minutes, and then heated to a molten state and drawn to obtain a composite fiber; wherein the weight ratio of the glass fiber, polypropylene fiber and fatty alcohol polyoxyethylene ether is 1:(0.3-0.8):(1-1.2).
2. The lightweight high-strength foamed concrete according to claim 1, characterized in that: The method for preparing the concrete comprises the following steps: Step A, mixing silicate cement, fly ash, quartz sand, composite fiber and water to obtain cement slurry; Step B, adding water to the composite foaming agent to foam in a foaming machine, adding it to the cement slurry obtained in step A and mixing evenly, then adding silica sol and hydroxypropyl methylcellulose, mixing evenly, pouring it into a mold, steam curing after molding, and obtaining concrete.
Citation Information
Patent Citations
Composite concrete foaming agent based on animal protein modification
CN115286282A
Anti-crack dry-mixed mortar taking Yellow River sand as raw material and preparation process of anti-crack dry-mixed mortar
CN117417159A
Lightweight foam concrete
CN117964305A